Social protection as a strategy for HIV prevention, education promotion and child marriage reduction among adolescents: a cross-sectional population-based study in Lesotho - Lucas Hertzog; Lucie Cluver; Boladé Hamed Banougnin; Maria Granvik Saminathen; Madison T. Little; Martina Mchenga; Rachel Yates; William Rudgard; Laura Chiang; Francis B. Annor; Viani Picchetti; Greta Massetti; et al. (BMC, 2024)
Abstract Background Lesotho's government has shown consistent efforts to implement social protection programmes. However, while recent evidence established a positive causal relationship between some of these programmes and food security there is little evidence on the extent to which these initiatives are associated with better educational and sexual and reproductive health outcomes among vulnerable adolescents in Lesotho. Methods and Findings The study uses cross-sectional, nationally representative data from the 2018 Lesotho Violence Against Children and Youth Survey. Our research examined the association between social protection receipt and educational and sexual and reproductive health outcomes among adolescents and young people (13-24 years) living in poverty. We employed multivariate logistic regression controlling for age, orphanhood, HIV status and sex. Social protection receipt was defined as household receipt of financial support from a governmental, non-governmental, or community-based program that provides income. Additionally, we fitted a marginal effects model by sex. Among the 3,506 adolescent females and males living in the two lowest poverty quintiles, receipt of social protection was associated with improvements in multiple adolescent outcomes: higher odds of consistent condom use (aOR 1.64, 95% CI 1.17-2.29), educational attainment (aOR 1.79, 95% CI 1.36-2.36), and school enrolment (aOR 2.19, 95% CI 1.44-3.34). Stratified analyses by sex showed that social protection receipt was also associated with reduced likelihood of child marriage among females (aOR 0.59, 95% CI 0.42-0.83) and higher odds of educational attainment and school enrolment among males (aOR 2.53, 95% CI 1.59-4.03 and aOR 3.11, 95% CI 1.56-6.19, respectively). Conclusions Our study provides evidence that social protection programs are associated with improved educational, sexual and reproductive health and child marriage prevention outcomes among adolescents living in poverty. Implementing and expanding such social protection initiatives could prove instrumental in improving the well-being of vulnerable adolescents. Contributions Social protection programs have been increasing in sub-Saharan African countries, playing a pivotal role in poverty reduction, with Lesotho being no exception. Despite the optimistic outlook brought about by the implementation of the National Social Protection Strategy Lesotho I (2014-19) and II (2021-2031), the impact of these programs on some specific outcomes that concern the lives of the most vulnerable adolescents in Lesotho remains to some extent unexplored. Additionally, Lesotho grapples with high rates of HIV, adolescent pregnancy, child marriage and early school dropout, which can further contribute to poor long-term health and social outcomes among adolescents. In this study, we used data from the 2018 Lesotho Violence Against Children and Youth Survey (VACS) to examine the association between receiving social protection and multiple adolescent outcomes: educational, sexual and reproductive. The findings revealed that social protection programs, particularly the existing government-provided cash transfers, are significantly associated with multiple better outcomes among adolescents living in the poorest households in Lesotho. Such cash transfer schemes in Lesotho are associated with improved sexual and reproductive health outcomes for adolescent females, including reduced child marriage rates, and improved educational outcomes for males. These findings indicate that government-led social protection programmes are positively associated with favourable outcomes that can improve the quality of life for adolescents in resource-limited settings.